Childhood Onset Urticaria Pigmentosa: A Case Report from Indonesian Setting - Gustia, Rina; Akhyar, Gardenia; Sugiharto, Audi (Journal of Pakistan Association of Dermatologists, 2023)
Background: Urticaria pigmentosa (UP) is a rare skin disease caused by increased deposition of clonal mast cell in the skin. C-kit gene mutation is thought to be the cause of UP. The three components of management include therapeutic aspects, counseling, and avoidance of triggering factors that might activate mast cell degranulation. Case report: we reported one case of UP in a 1-year-old boy with a 7-month history of generalized pruritic brownish patches. Dermatological examination revealed generalized hyperpigmented macules, patches and a positive darier’s sign. Histopathological examination showed epidermal melanin deposition in the basal layer and mast cell infiltration in the dermal layer which highlighted positively with Giemsa staining. Complete hematology and liver function test were within normal ranges which exclude possibility of internal organ involvement. The initial SCORMA score was 53.4. Patient was treated with a combination of sedative and non-sedative H1-antihistamines with remarkable improvement of the symptoms (SCORMA 39.2). Discussion: Urticaria pigmentosa is rare. Limited definitive data has been obtained regarding the prevalence and clinical profile of this disease. Urticaria pigmentosa most commonly affects children and more than 50% of cases occur before the age of 2 years. The prognosis of UP depends on patientâ€™s age, disease severity, and clinical subtype. In 50-60% of cases will improve during adolescence. Key word: cutaneous mastocytosis, mast cell, darier’s sign